The Behavior of Medical Record Officers at Mamuju Tengah General Hospital - Marhawati, Marhawati; Umar, Sitti Mawaddah; Wahyuningsih, Sri (Gema Wiralodra, 2025)
The management of medical records at Mamuju Tengah General Hospital in 2016 was still conducted manually, with the completeness of medical records ranging from 60-80%. This study aims to describe the behavior of medical record officers at the hospital. Using a descriptive quantitative method, a sample of 38 medical record officers was selected using a saturated sampling technique. The research instrument used was a structured questionnaire that had been tested for validity and reliability. The type of data collected consisted of primary data obtained directly from respondents’ answers, and secondary data in the form of hospital documentation related to medical records management. Data analysis was performed using univariate descriptive statistics, presented in frequency distributions and percentages. The results showed that the knowledge of the officers (52.6%) and their actions (63.2%) were still inadequate. Additionally, the facilities and infrastructure in the medical records installation were also lacking (76.3%). However, the officers' perceptions of the standard operating procedures (65.8%) were considered good. It is recommended that the officers receive training, improve the facilities and infrastructure, and enhance the socialization of SOPs to improve the quality of medical record management.